Germany's social market economy: A blueprint for Latin American countries? - Dirk Sauerland (Universität Witten/Herdecke, Fakultät für Wirtschaftswissenschaft, 2015)
[Introduction ...] This paper tries to answer these questions taking five steps of argumentation. Firstly, the paper briefly sketches the theoretical and empirical background of the modern liberal market economy concept. Secondly, it outlines in more detail the basic ideas of the ordoliberal social market economy concept and some modern amendments to this concept based on institutional economics' ideas. Thirdly, the paper compares the two concepts and it uses institutional data to describe two prototypes of economies based on those concepts of the United States and Germany. Fourthly, the same databases are used to describe the institutional status quo in five Latin American countries. The fifth and last step of the argumentation discusses the limitations of a simple blueprint idea with regards to economic orders. The paper ends with conclusions on options and limits of taking the liberal or the social market economy concept as a blueprint for Latin American countries.
Keywords: 330; Soziale Marktwirtschaft; Wirtschaftsliberalismus; Ordnungsökonomik; Legitimität; Institutionenökonomik; Vergleich; Deutschland; Lateinamerika; USA